International Environmental Law and Governance. - Fitzmaurice, Malgosia (Queen Mary studies in international law ;, 2015)
The book analyzes the question of legitimacy and efficacy of certain organs created on the basis of Multilateral Environmental Agreements (Conferences and Meetings of the Parties) from the point of view of their structural invocation and analyzing their new developments regarding the powers of these bodies in achieving desired goals of environmental protection, and the necessary international collaboration to achieve it.